2019
DOI: 10.1002/ccd.28373
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in procedural and clinical outcomes following rotational atherectomy

Abstract: Aim: Evaluate sex differences in procedural net adverse clinical events and long-term outcomes following rotational atherectomy (RA).Methods and Results: From August 2010 to 2016, 765 consecutive patients undergoing RA PCI were followed up for a median of 4.7 years. 285 (37%) of subjects were female. Women were older (mean 76 years vs. 72 years; p < .001) and had more urgent procedures (64.6 vs. 47.3%; p < .001). Females received fewer radial procedures (75.1 vs. 85.1%; p < .001) and less intravascular imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 28 publications
(20 reference statements)
7
20
1
Order By: Relevance
“…An analysis of RA use from 2014 to 2020 in the entire group of patients undergoing PCI, based on a large national registry, confirms that the upward trend in RA percentage among all PCI procedures continues [14,18]. Like in previously published articles, in the current analysis, we demonstrated that women treated with PCI and RA were older than men and presented acute coronary syndrome (ACS) more often [19]. While there were no significant differences in vascular access, in other publications, it was suggested that female patients were more often treated from femoral vascular access [19].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…An analysis of RA use from 2014 to 2020 in the entire group of patients undergoing PCI, based on a large national registry, confirms that the upward trend in RA percentage among all PCI procedures continues [14,18]. Like in previously published articles, in the current analysis, we demonstrated that women treated with PCI and RA were older than men and presented acute coronary syndrome (ACS) more often [19]. While there were no significant differences in vascular access, in other publications, it was suggested that female patients were more often treated from femoral vascular access [19].…”
Section: Discussionsupporting
confidence: 84%
“…Like in previously published articles, in the current analysis, we demonstrated that women treated with PCI and RA were older than men and presented acute coronary syndrome (ACS) more often [19]. While there were no significant differences in vascular access, in other publications, it was suggested that female patients were more often treated from femoral vascular access [19]. According to multivariable analysis, a greater burden of periprocedural cardiovascular death and complications was presented in female patients, which is in accordance with the data from previously published papers [19].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Retrospective analyses of trial data evaluating RA have demonstrated that women are at increased risk of procedural complications and major adverse cardiac events (MACE) compared with men. 124 In a recent propensity matched series of 765 consecutive patients (37% women) undergoing RA followed for a median of 4.7 years, the primary endpoint of net adverse cardiac events (net adverse clinical events: all-cause death, myocardial infarction, stroke, and target vessel revascularization plus any procedural complication) occurred more often in women (15.1 vs. 9.0%; adjusted OR 1.81, 95% CI 1.04-3.13, p¼0.037). This was driven by an increased risk of procedural complications rather than procedural MACE.…”
Section: Atherectomy Devicesmentioning
confidence: 99%
“…In line with these observations are data from a recent registry [11] showing that women had a higher rate of myocardial infarction at one year following complex PCI (even after adjusting for potential confounders), even though they present with less challenging lesions than men. Moreover, Ford et al [12] showed that women undergoing RA PCI are at greater risk of bleeding complications and coronary perforations leading to cardiac tamponade.…”
mentioning
confidence: 99%